Analisis Perilaku Pola Retak Balok Beton Bertulang - Rendy Wijaya; Reni Suryanita; Ismeddiyanto Ismeddyanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Concrete is the common material that is used on construction. Concrete will be subjected to loading during the construction until its service time. Continuous loading on concrete caused cracks in concrete. Cracks can also occur due to be changes in temperature, shrinkage, and also when the concrete was ready to casted that caused by cement hydration . The purpose of this study was to obtained crack patterns existed on reinforced concrete beam during the application of flexural load. The specimen used on this study was reinforced concrete beam with the cross section of 10 cm x 20 cm and with the length of 125 cm. The upper and lower longitudinal reinforcement for the beam was 2D8 and 2D10 respectively. The shear reinforcement of the beam was D6-167. The result of this study was found that the crack pattern that occurred was a flexural crack. Keywords: concrete, cracks, reinforcement, flexural crack.